The effect of heart variability biofeedback training for improving cognitive performance among female manufacturing operators - Sutarto, Auditya Purwandini (2011)
nufacturing environment, performance at the operative level becomes more critical because of predominantly cognitive tasks assigned and less importance of human manual control. Moreover, most operators perform their cognitive functions below their peak performance due to many reasons such as fatigue, boredom, and stress. To date there has not been much research conducted on the use of biofeedback training for cognitive performance enhancement. Heart rate variability (HRV) biofeedback shows potential application in performance enhancement. The objective of this study is to examine the effect of HRV biofeedback training for the improvement of cognitive performance in electronic manufacturing operators industry. Subjects consisted of 36 female operators from an electronic manufacturing factory in Kuantan, Malaysia who were randomly assigned as the experimental group (n = 19), and control group (n = 17). The intervention participants received five session of weekly HRV biofeedback training of 30-50 minutes each. Physiological stress profiles, cognitive performance, and self-reports questionnaire (Depression, Anxiety, and Stress Scale) were assessed before and after the intervention. Results of two-way repeated measures ANOVA indicated that there were significant group x time interaction effects for attention, memory, and cognitive flexibility. Within group analysis using paired t-tests revealed that, as opposed to the control group, the intervention group improved significantly on all cognitive measures. The training participants also showed decrease on depression, anxiety, and stress (all p<0.01). Significant within-group improvements were also found for the biofeedback participants during physiological stress profile in percentage of LF activity and breaths perminute. Further, the biofeedback group showed significant increase in LF activity, SDNN, and slower breathing rate throughout five sessions. The HRV data confirms that the participants learned how to effectively manipulate and control activity in the autonomic nervous system. Similar significant results did not exist in the control group.In summary, this study provides potential application of HRV biofeedback for operator’s cognitive performance enhancement,inparallel with increase HRV.